Chiroptical study of cryptophanes subjected to self‐encapsulation. Issue 7 (28th May 2019) - Baydoun, Orsola; Buffeteau, Thierry; Daugey, Nicolas; Jean, Marion; Vanthuyne, Nicolas; Chapellet, Laure‐Lise; De Rycke, Nicolas; Brotin, Thierry
Abstract: In 1, 1, 2, 2‐tetrachloroethane‐ d 2, the 129 Xe NMR spectrum of the Xe@cryptophane‐223 complex bearing seven acetate groups (Xe@1 complex) shows an unusually broad signal compared with that of its congeners (Chapellet, LL. et al. J. Org. Chem . 2015 ;80:6143–6151). To interpret this unexpected behaviour, a 1 H NMR analysis and a thorough study of the chiroptical properties of 1 as a function of the nature of the solvent have been performed. The 1 H NMR spectra of 1 reveal that a self‐encapsulation phenomenon takes place in DMSO‐ d 6 and 1, 1, 2, 2‐tetrachloroethane‐ d 2 solvents. Thanks to the separation of the two enantiomers of 1 by HPLC on chiral stationary phase, the two enantiomers of 1 have been studied in detail by polarimetry, electronic (ECD), and vibrational (VCD) circular dichroism spectroscopies. Except for ECD spectroscopy, these chiroptical techniques reveal spectroscopic changes as a function of the nature of the solvent. For instance, in DMSO and 1, 1, 2, 2‐tetrachloroethane, in which the self‐encapsulation phenomenon takes place, the sign of the specific optical rotation of [CD(−)254 ]‐1 and [CD(+)254 ]‐1 is changed. These results have then been compared with those obtained with cryptophane‐223 bearing only one acetate group on the propylenedioxy linker (compound 2 ) and with cryptophane‐223 bearing six acetate groups (compound 3 ). A self‐encapsulation phenomenon is also observed with compound 2 . Finally, compounds 2 and 3 show different chiroptical properties compared with those obtained with the two enantiomers of compound 1 . Abstract :